Polymeric Hydrogel Coating for Modulating the Shape of Keratin Fiber - Wang, Lanlan; Cavaco-Paulo, Artur; Xu, Bo; Martins, Madalena (Frontiers in Chemistry, 2019)
Hydrogel coating was explored to modulate the shape of keratin hair fiber. The motivation was the development of an eco-friendly methodology with non-toxic chemicals to modulate keratin fiber. Polymeric hydrogel of acrylic acid and N-N-dimethylacrylamide was prepared by free-radical polymerization in aqueous solution, using nano-alumina particles as crosslinker and potassium persulfate as an initiator. Physico-chemical properties of the hydrogel was investigated by Fourier transformer infrared spectrum (FTIR), thermal analysis and swelling ratio behavior. After hydrogel coating, morphological modification was observed from straight to curly hair effect. The influence of hydrogel coating on hair fiber was evaluated by perming efficiency supported by X-ray diffraction and morphological characterization (SEM and AFM). The durability of hydrogel coating was tested until four wash processes maintaining around 65% the new configuration of the hair fiber.